Prevalence and molecular analysis of Toxocara cati in Baghdad Province - Alani, Zaid Khalid; Kawan, May Hameed (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This study aimed to detect Toxocara cati in cats by microscopic and molecular analysis using PCR, sequencing, and phylogenetic analysis. Materials and Methods: Randomly selected 200 cat feces samples were taken from various private veterinarian clinics in Baghdad. To identify eggs of T. cati by the flotation method, DNA from 100 cat feces was extracted, and one pair of ITS2 region-specific primers was used for polymerase chain reaction, followed by sequencing. Results: Toxocara cati infection rate was found to be 23 out of 100 fecal samples using PCR. Ten DNA product sequence data studies showed 98%–100% similarity to the 5.8S ribosomal RNA gene sequences found in the Gene Bank. The study incidence showed that the overall infection rate by microscopic examination was 23%, with no significant difference between stray cats (27%), and domestic cats (19%). After studying the effect of several epidemiological parameters on the infection rate, it was found that the infection rates of stray and domestic cats were higher in kittens under six months of age, at 46.1% and 27%, respectively, whereas rates were lower for the adult than six months was 11.5% of domestic cats and 14.7% of stray cats. The percentage of stray and domestic male cats that were registered was 35.5%, whereas the female cats registered were 20.6% and 17.5%, respectively. Conclusion: Cats are significant clinical reservoirs for zoonotic parasites. In Iraq, Baghdad has a high incidence of T. cati detections. Compared to conventional methods, PCR is thought to be a more sensitive, accurate diagnostic procedure that confirms the species’ identity. Adv. Vet. Anim. Res., 11(2): 392-397, June 2024 http://doi.org/10.5455/javar.2024.k788